Annotated list of the scale insects of Guatemala - Williams, Michael L. (ENTOMOLOGIA HELLENICA, 2010)
An annotated checklist of the soft scale insects (Hemiptera: Coccidae) is given for the Central American country of Guatemala. Host and locality data is presented for each species, along with notes on its taxonomic status. The list was developed from study of materials collected in Guatemala by the author and others during the years 1990-2007, and from a review of the literature and records and slide material in the United States National Museum Coccoidea Collection. A study of these materials has increased the number of soft scale insects currently known from Guatemala to 29 species belonging to 23 genera. Guatemala currently ranks second in the number of soft scale insects known from Central American countries below Panama, which has 36 recorded species belonging to 18 genera.